Prognostic impact of the post-treatment T cell composition and spatial organization in soft tissue sarcoma patients treated with neoadjuvant hyperthermic radio(chemo)therapy - Rupp, Luise; Resag, Antonia; Potkrajcic, Vlatko; Warm, Verena; Wehner, Rebekka; Jöhrens, Korinna; Bösmüller, Hans; Eckert, Franziska; Schmitz, Marc (Frontiers in Immunology, 2023)
Soft tissue sarcomas (STS) form a heterogeneous group of tumors sharing a mesenchymal origin. Despite good local control of the disease, the occurrence of distant metastases often limits survival of STS patients with localized, high-risk tumors of the extremities. Accumulating evidence suggests a central role for the tumor immune microenvironment in determining the clinical outcome and response to therapy. Thus, it has been reported that STS patients with a high immune signature and especially presence of B cells and tertiary lymphoid structures display improved overall survival and response to checkpoint inhibitor treatment. Here, we explored the effect of curative multimodal therapy on the T cell landscape of STS using multiplex immunohistochemistry. We analyzed the phenotype, frequency, and spatial distribution of STS-infiltrating CD8+ T cells by staining for CD8, 4-1BB, Granzyme B, Ki67, PD-1, and LAG-3 as well as CD3+ T helper cells using a panel consisting of CD3, T-bet, GATA3, RORγT, FoxP3, and Ki67. All patients received neoadjuvant radiotherapy plus locoregional hyperthermia with or without chemotherapy. While the treatment-naïve biopsy sample allows an analysis of baseline T cell infiltration levels, both intra- and peritumoral areas of the matched resected tissue were analyzed to assess composition and spatial distribution of the T cell compartment and its therapeutic modulation. Generally, post-treatment tissues displayed lower frequencies of CD3+ and CD8+ T cells. Association with clinical data revealed that higher post-treatment frequencies of peritumoral and intratumoral CD3+ T cells and intratumoral PD-1+ CD8+ T cells were significantly associated with improved disease-free survival (DFS), while these densities had no prognostic significance in the biopsy. Upon spatial analysis, a high ratio of intratumoral to peritumoral CD8+ T cells emerged as an independent prognostic marker for longer DFS. These results indicate that the STS T cell landscape is altered by multimodal therapy and may influence the clinical outcome of patients. An enhanced understanding of the STS immune architecture and its modulation by neoadjuvant therapy may pave the way towards novel treatment modalities and improve the long-term clinical outcome of STS patients.